2022
DOI: 10.32604/csse.2022.017003
|View full text |Cite
|
Sign up to set email alerts
|

Relative Time Quantum-based Enhancements in Round Robin Scheduling

Abstract: Modern human life is heavily dependent on computing systems and one of the core components affecting the performance of these systems is underlying operating system. Operating systems need to be upgraded to match the needs of modern-day systems relying on Internet of Things, Fog computing and Mobile based applications. The scheduling algorithm of the operating system dictates that how the resources will be allocated to the processes and the Round Robin algorithm (RR) has been widely used for it. The intent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The first process in the queue is selected, and the CPU is allocated for the chosen TQ. Then the remaining burst times are moved to the tail of the ready queue [21]. Sometimes the first process is too large and the rest processes are too small, so the response time decreases which causes an increase in waiting time and turnaround time.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The first process in the queue is selected, and the CPU is allocated for the chosen TQ. Then the remaining burst times are moved to the tail of the ready queue [21]. Sometimes the first process is too large and the rest processes are too small, so the response time decreases which causes an increase in waiting time and turnaround time.…”
Section: Related Workmentioning
confidence: 99%
“…For interactive users, these environments must ensure reasonable response times. In the RR scheduling algorithm, every process in the ready queue receives a time slice (time quantum (TQ)) [21]. The current process is placed at the end of this ready queue when the TQ expires.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that machine learning could be used to improve AKI diagnosis and ultimately improve patient outcomes (Gluck and Gostin, 2023). (Iqbal et al, 2022) highlights the potential benefits of time-based enhancements in scheduling algorithms, which can be relevant for optimizing the execution of machine learning algorithms in healthcare analytics. A systematic review published in the Journal of Medical Internet Research examined the use of machine learning in predicting patient outcomes in cancer care (Wolinetz and Tabak, 2023).…”
Section: Machine Learning Influence On Patientmentioning
confidence: 99%
“…In this section, we will review the relevant literature on scheduling algorithms, explicitly focusing on the approaches of dynamic time quantum and priority scheduling. For example, the authors in [1] proposed the design of four versions of the Round Robin scheduling algorithm that allows for the dynamic determination of the time quantum based on the candidate process's overall execution time. The main goal of these variations was to achieve a fair distribution of time quantum among the processes to increase the system's overall performance.…”
Section: Related Workmentioning
confidence: 99%
“…The process is then allocated memory and system resources and added to the scheduler's queue. The scheduler decides which method to execute next based on the scheduling algorithm [1][2][3][4]. Therefore, various scheduling algorithms are proposed to address this problem, each with its trade-offs and advantages.…”
Section: Introductionmentioning
confidence: 99%